IMPLEMENTATION MODEL OF BANDUNG STUNTING RESPONSE PROGRAM WITH SAFE AND HEALTHY FOOD (BANDUNG TANGINAS) IN KARANG PAMULANG VILLAGE, BANDUNG CITY - Sait - Abdullah (Dialogue : Jurnal Ilmu Administrasi Publik, 2025)
This study was conducted to analyze the implementation of the Bandung Tanginas program in the Karang Pamulang Village area using the  Van  Meter and Van Horn implementation model theory which has 6 (six) variables in it consisting of: Policy Standards  and  Objectives, Resources, Communication, Characteristics of Implementing Agents, Economic, Social, and  Political Environment, and Implementing Attitudes. by using the method of approach qualitative research through interviews and documentation studies. The findings in the research on  the implementation of the  Bandung Tanginas program in Karang Pamulang Village have not shown good enough performance because  in  its  implementation there are   still several obstacles ranging from the selection of beneficiaries that are not in accordance with the targets and standards, consistency in the implementation time of the program,  to community involvement in its implementationto achieve the objectives of the Bandung Tanginas program, namely providing additional food ingredients to pregnant women, breastfeeding mothers, and children under two years old who fall into the underprivileged category so as to prevent and overcome stunting problems in the city of Bandung, especially Karang Pamulang Village. Therefore, based on research that has been conducted using Van Meter and Van Horn implementation model theory, researchers provide recommendations for implementation models that can be used to improve the performance of the Bandung Tanginas program in Karang Pamulang Village. The proposed recommendations for the Bandung Tanginas program provide efforts that can be made by the village to implement the Bandung Tanginas program.